2009
DOI: 10.1007/s00134-009-1619-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical risk predictive rules for invasive candidiasis in a prospective multicentre cohort of ICU patients

Abstract: Risk predictive models should factor in both clinical risk factors and Candida colonisation parameters. Integrating these models into therapeutic algorithms first requires external validation in different patient populations and settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Based on a cut-off of a score of 3, the sensitivity was 78% (81% in development data), specificity was 66% (74% in development data), and PPVs and NPVs were 14% and 98%, respectively (not reported in development data). Playford et al 46 validated four clinical decision rules -the best rule from Ostrosky-Zeichner et al 27 and a subsequent revision to this, published in abstract form, and the two best rules from Pittet et al 43 -in a prospective cohort of 615 patients admitted for at least 72 hours to four multidisciplinary ICUs in Australia. Performance of the clinical prediction rules was worse than in the development data sets and the authors recommended that to identify a sufficiently high-risk population to consider for antifungal therapy would require a combination of the clinical risk factors from Ostrosky-Zeichner et al 27 with measures of colonisation from Pittet et al 43 Most recently, Hermsen et al 47 set out to validate the clinical decision rules of Paphitou et al 28 and Ostrosky-Zeichner et al 27 in a case-control study of 88 cases and 264 matched control subjects staying at least 4 days in a single multidisciplinary ICU in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a cut-off of a score of 3, the sensitivity was 78% (81% in development data), specificity was 66% (74% in development data), and PPVs and NPVs were 14% and 98%, respectively (not reported in development data). Playford et al 46 validated four clinical decision rules -the best rule from Ostrosky-Zeichner et al 27 and a subsequent revision to this, published in abstract form, and the two best rules from Pittet et al 43 -in a prospective cohort of 615 patients admitted for at least 72 hours to four multidisciplinary ICUs in Australia. Performance of the clinical prediction rules was worse than in the development data sets and the authors recommended that to identify a sufficiently high-risk population to consider for antifungal therapy would require a combination of the clinical risk factors from Ostrosky-Zeichner et al 27 with measures of colonisation from Pittet et al 43 Most recently, Hermsen et al 47 set out to validate the clinical decision rules of Paphitou et al 28 and Ostrosky-Zeichner et al 27 in a case-control study of 88 cases and 264 matched control subjects staying at least 4 days in a single multidisciplinary ICU in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, no previous study has assessed the costeffectiveness of using a risk model to define a risk threshold above which to initiate antifungal prophylaxis for preventing invasive Candida infection in non-neutropenic, critically ill adult patients. 46 This chapter therefore presents an economic evaluation with the aim to report the relative costeffectiveness of alternative strategies to prevent invasive Candida infection for non-neutropenic, critically ill adult patients admitted to NHS critical care units. The objectives of the economic evaluation were to establish the relative cost-effectiveness of risk assessment using the FIRE Study risk models, followed by initiation of prophylaxis at different thresholds of baseline risk and at different time points; and to assess the relative value of further research to reduce uncertainty about the optimum strategy to adopt.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from mixed medical/surgical ICUs in Australia, we demonstrated that the post hoc addition of colonization parameters to two published clinical risk factor-only predictive models improved their performance characteristics (17).…”
mentioning
confidence: 98%
“…Those rules have been applied in various settings and have included assessment at different times postadmission to the ICU and different types of ICU (surgical ICUs only or mixed medical/surgical ICUs-defined as units that house both medical and surgical populations). These differences may explain why predictive models and algorithms have performed poorly outside their derivative populations (17).…”
mentioning
confidence: 99%
“…[7][8][9] These studies have focused on patients at high risk for IC and have included colonization sites other than the gastrointestinal tract. Additionally, the ability to include colonization with yeast in such a clinical prediction rule requires routine surveillance cultures, which are not performed at our institution.…”
Section: Conflict Of Interestmentioning
confidence: 99%